2020
DOI: 10.1037/dev0000907
|View full text |Cite
|
Sign up to set email alerts
|

A four-wave, cross-lagged model of problematic internet use and mental health among Chinese college students: Disaggregation of within-person and between-person effects.

Abstract: Based on 4 annual waves of data from a large sample of Chinese college students (N ϭ 2,329, M age ϭ 18.40 years old, SD ϭ .85; 63.10% females), this study examines the within-person and between-person effects in the association between problematic Internet use (PIU) and mental health issues. Results of analyses using the developmental equilibrium model (i.e., an autoregressive, cross-lagged panel model) demonstrate a reciprocal positive association between PIU and mental health issues consistently across waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 56 publications
3
28
1
2
Order By: Relevance
“…The influence of returning to their families and the fact that the study population live in small cities seem to be essential to understanding the results of the present study, since they contradict other research, which found an increase in anxiety levels among university students in several countries (Akdeniz et al, 2020;Cornine, 2020;Wang et al, 2020;Zhou et al, 2020). In our study, we recorded a reduction in anxiety trait expression.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The influence of returning to their families and the fact that the study population live in small cities seem to be essential to understanding the results of the present study, since they contradict other research, which found an increase in anxiety levels among university students in several countries (Akdeniz et al, 2020;Cornine, 2020;Wang et al, 2020;Zhou et al, 2020). In our study, we recorded a reduction in anxiety trait expression.…”
Section: Discussioncontrasting
confidence: 82%
“…In order to reduce virus transmission, social distancing and home confinement were recommended by health authorities and governments (Lakhan et al, 2020;Parlapani et al, 2020;Tang et al, 2020). However, distancing measures, even when added to activation of this behavioral immune system, may have a negative effect on the social life and emotional state of individuals (Ackerman et al, 2020;Akdeniz et al, 2020;Cornine, 2020;Di Renzo et al, 2020;Ingram et al, 2020;Shigemura et al, 2020;Volino-Souza et al, 2020;Wang et al, 2020;Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anxiety of the respondents might be result in switching to online education, working from home as much as possible in business life, reducing working hours, social distancing, and other social measures taken across the country. Recent research has indicated that the delay in academic activities was related to the emergence of anxiety symptoms with university students in China ( 28 ). Another study has demonstrated that college students’ anxiety about COVID-19 might have been related to the effect of the coronavirus disease on their studies ( 29 ) and future employment ( 6 ).…”
Section: Dıscussıonmentioning
confidence: 99%
“…No entanto, o cenário se modificou completamente. Para reduzir a propagação e transmissão do vírus, o distanciamento social, o confinamento em casa e outras medidas, foram recomendados pelas autoridades de saúde e do governo (Lakhan et al, 2020;Parlapani et al, 2020), porém, apesar de protetivas, tais medidas afetaram negativamente a vida social e o estado emocional das pessoas, propiciando um aumento expressivo da ansiedade (Akdeniz et al, 2020;Cornine, 2020;Shigemura et al, 2020;Volino-Souza et al, 2020;Wang et al, 2020;Zhou et al, 2020).…”
Section: Introductionunclassified